Altered Neuronal Activity Topography Markers in the Elderly with Increased Atherosclerosis - Shibata, Takashi; Musha, Toshimitu; Kosugi, Yukio; Kubo, Michiya; Horie, Yukio; Kuwayama, Naoya; Kuroda, Satoshi; Hayashi, Karin; Kobayashi, Yohei; Tanaka, Mieko; Matsuzaki, Haruyasu; Nemoto, Kiyotaka; et al. (Frontiers in Aging Neuroscience, 2017)
Background: Previously, we reported on vascular cognitive impairment (VCI) templates, consisting of patients with VCI associated with carotid stenosis (>60%) using a quantitative electroencephalographic (EEG) technique called neuronal activity topography (NAT). Here using the VCI templates, we investigated the hypothesis that internal carotid artery–intima-media thickness (ICA–IMT) is associated with EEG spectrum intensity (sNAT) and spectrum steepness (vNAT). Methods: A total of 221 community-dwelling elderly subjects were recruited. Four groups were classified according to quartiles of ICA–IMT as assessed by ultrasonography: control group A, normal (≤0.9 mm); group B, mild atherosclerosis (1−1.1 mm); group C, moderate atherosclerosis (1.2−1.8 mm); and group D, severe atherosclerosis (≥1.9 mm). EEG markers of power ratio index (PRI), and the binary likelihood of being in the VCI group vs. the that of being in control group A (sLx:VCI−A, vLx:VCI−A) were assessed, respectively. Differences in mean total scores for PRI, sLx:VCI−A, vLx:VCI−A, between control group A and the other groups were compared using Dunnett's test, respectively. Results: The mean total scores of the PRI were 3.25, 3.00, 2.77, and 2.26 for groups A, B, C, and D, respectively. There was a significant decrease in the PRI in group D compared with group A (P = 0.0066). The mean total scores of the sLx:VCI−A were −0.14, −0.11, −0.1, and −0.03 for groups A, B, C, and D, respectively. The sLx:VCI−A in group D was significantly higher compared to that in group A (P < 0.0001). The mean total scores of the vLx:VCI−A were −0.04,−0.01, 0.01, and 0.06 for group A, B, C, and D, respectively. The vLx:VCI−A in group D and group C was significantly higher compared to that in group A, respectively (P < 0.0001, P = 0.02). Conclusion: Community-dwelling elderly subjects in the increased carotid atherosclerosis of ICA–IMT (≥1.9 mm) were at greatest risk of an EEG change as assessed by NAT.